Prevalence and Characterization of Fatigue in Patients with Skin Diseases - Laurent Misery; Jason Shourick; Charles Taïeb (Medical Journals Sweden, 2020)
The aim of this study was to examine the prevalence and nature of fatigue in patients with skin diseases by comparison with controls, using a survey of a large representative sample of the French population (n = 2,502). Of the respondents, 659 reported having a skin disease and 1,843 did not. Quality of life was decreased in people with skin diseases compared with controls, while levels of stress and sleep deprivation were higher in people with skin diseases. Level of fatigue was higher in people with skin diseases than in controls. The relative risk of fatigue was 4.71 (3.44-5.98, p <0.001). Mediation analysis, adjusted according to sex, age and each skin disease, showed that the effects of skin diseases on fatigue were more commonly direct than indirect. To our knowledge, this is the first study to demonstrate that patients with skin diseases experience fatigue more frequently and more intensely. Hence, fatigue should be used as a new patient-related outcome in clinical trials.